PERKAWINAN BEDA AGAMA PERSPEKTIF MAJELIS ULAMA INDONESIA - Basit Misbachul Fitri, Abdul; Sholeh, Moh. Badrus (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2022)
Indonesia is a plural country, the people have different religions. This is in accordance with Article 29 paragraph 2: "The state guarantees the freedom of everyone to embrace their respective religions and to worship according to their religion and beliefs. Mixed marriages are marriages between people who in Indonesia are subject to different laws. Different laws can occur because of religious differences (interreligeus) such as marriages between Muslims and Christians, or because of differences in law because of differences in countries. This article focuses on the study of interfaith marriages according to the fatwa mui, by providing a comparison with the law according to several religions in addressing interfaith marriages. The purpose of this article is to provide an understanding and explanation of interfaith marriages which are still being debated in society. In the context of the Islamic view, it is forbidden to marry people who are not of the same religion, in principle Protestantism, Catholicism, Hinduism, Buddhism, and Confucianism forbid PBA even though there is a dispensation to continue. Interfaith marriages are haraam and illegitimate. The marriage of Muslim men and women of Ahl al-Kitab, according to qaul mu'tamad, is haraam and illegitimate. This is also in accordance with the MUI fatwa.